Effect of Intravenous Dexamethasone in Combination with Caudal Analgesia on Post Operative Pain Control after Herniotomy in Children (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Dexamethasone has a powerful anti-inflammatory action and has demonstrated reduced morbidity after surgery.Objectives: The aim of this study was to examine the effects of a single i.v. dose of dexamethasone in combination with caudalblock on postoperative analgesia in children.Methods: This study was a randomized, double blind clinical trial, in which 77 children of ASA I and II, aged 3-10 years, undergoing elective unilateral herniotomy operation, was allocated in a double blind manner. Control Group I consist of 39 patients and Dexamethasone Group II consists of 38 patients. Group II received i.v. Dexamethasone 0.5 mg/Kg (Maximum 20 mg) and Group I received the same volume of i.v. saline after induction of anaesthesia. After inhalation induction of general anaesthesia, children received either dexamethasone 0.5-1 mg/Kg (maximum 20 mg) (n=39) or the same volume of saline (n=38) i.v. A caudal anaesthetic block was then performed using 1.5 ml/kg of Bupivacaine 0.25% in all patients. After surgery, rescue analgesic consumption, pain scores, and adverse effects were evaluated for 24 h.Results: Significantly, fewer patients in the dexamethasone group required fentanyl for rescue analgesia (7.9% vs38.5%, p